Last night at the Lobster - O'Nan, Stewart, 1961- (Viking, 2007)
Managing a failed seafood restaurant in a run-down New England mall just before Christmas, Manny DeLeon coordinates a challenging final shift of mutinous staff members, an effort that is complicated by his love for a waitress, a pregnant girlfriend, and an elusive holiday gift.